Pertanggungjawaban Pidana Korporasi dalam Kejahatan Lingkungan Industri Ekstraktif di Indonesia: Antara Norma dan Implementasi dalam Perspektif Green Criminology - Dela Putri Dwinanda (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
The development of the extractive industry in Indonesia has contributed significantly to national economic growth, but has also caused serious impacts in the form of environmental damage and pollution. This study aims to analyze the regulation and application of corporate criminal liability for environmental crimes in the extractive industry sector, emphasizing the gap between legal norms and their implementation from a Green Criminology perspective. The research method used is normative legal research with a statutory and conceptual approach, through a literature study of primary, secondary, and tertiary legal materials analyzed qualitatively. The results show that normatively, corporate criminal liability has been comprehensively regulated in Law Number 32 of 2009 and strengthened in the 2023 Criminal Code. However, in law enforcement practice, there are still significant gaps, particularly in proving the elements of fault and the tendency for law enforcement to focus more on individual perpetrators than on corporations. The case study of nickel mining on Wawonii Island concretely demonstrates the discrepancy between legal norms and implementation in the field, which has resulted in environmental damage and social conflict. From a Green Criminology perspective, this condition reflects ecological losses and environmental injustice due to the dominance of economic interests. Therefore, firm and effective law enforcement is needed to ensure environmental protection.